Informed Bandwidth Adaptation in Wi-Fi Networks using Ping-Pair - Das, Rajdeep; Baranasuriya, Nimantha; Padmanabhan, Venkat; Rodbro, Christoffer; Gilbert, Seth (ACM CoNEXT 2017, 2017)
Bandwidth adaptation for real-time streaming applications is typically designed to be conservative, since pushing for higher bandwidth could be counterproductive if it means an increased latency. However, such bandwidth adaptation operates based on the "symptoms" of congestion (e.g., increased delay) without knowing the underlying cause (self-congestion vs. cross-traffic). In this paper, we consider this problem in the context of Wi-Fi networks and introduce a novel technique, Ping-Pair, to measure and attribute congestion. We have integrated Ping-Pair into the popular Skype audio-video conferencing application to enable improved bandwidth adaptation dubbed Kwikr, using which we have conducted controlled experiments and also randomized A/B tests in a production setting.